2021
DOI: 10.1371/journal.pone.0255610
|View full text |Cite
|
Sign up to set email alerts
|

Popular media as a double-edged sword: An entertainment narrative analysis of the controversial Netflix series 13 Reasons Why

Abstract: 13 Reasons Why is a Netflix original series adapted from Jay Asher’s 2007 young adult novel with the same title. Season 1 premiered on March 31, 2017 and featured the sensitive issue of teen suicide along with bullying, substance use, depression, and sexual assault. Unlike the typical teen dramas on popular streaming platforms, this show was created not only for entertainment, but also to stimulate conversations about taboo topics that people often shy away from. However, it also caused significant controversy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…The majority of sex content analyses on adolescent-directed content in previous research (e.g., Malacane & Martins, 2017; Signorielli & Bievenour, 2015) mainly focused on traditional television, thus excluding a key part of media content among contemporary adolescents (e.g., Netflix). The few exceptions are a study by Wang and Parris (2021) and a study by Maes and Vandenbosch (2022a). In Wang and Parris (2021), portrayals of sexual assault in the 13 episodes of season one of 13 Reasons Why were content analyzed.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of sex content analyses on adolescent-directed content in previous research (e.g., Malacane & Martins, 2017; Signorielli & Bievenour, 2015) mainly focused on traditional television, thus excluding a key part of media content among contemporary adolescents (e.g., Netflix). The few exceptions are a study by Wang and Parris (2021) and a study by Maes and Vandenbosch (2022a). In Wang and Parris (2021), portrayals of sexual assault in the 13 episodes of season one of 13 Reasons Why were content analyzed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, adolescents are increasingly attracted to streaming services (also known as Over-The-Top media services [OTT]) and Netflix is one of the most popular streaming services among adolescents (Rideout & Robb, 2019; Stoll, 2022). Netflix has also produced original series that are targeted to adolescents and depict adolescent lives (e.g., 13 Reasons Why , Sex Education ) and topics related to sex have been important parts of these series (e.g., Lauricella et al, 2018; Wang & Parris, 2021). Research has shown that for adolescents, exposure to sex content in the media can relate to several negative outcomes, such as earlier age of having first sexual intercourse (a risk factor of STD, Kaestle et al, 2005) and teen pregnancy (Collins et al, 2011; Martino et al, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The methodology within this framework has yet to be fully standardized [ 47 ]. Health communication studies have applied media framing through diverse methodologies: for example, Wang and Parris [ 48 ] combined framing theory with narrative analysis to examine the risks associated with the depiction of teenage suicide in the TV series 13 reasons why . Framing theory was combined with quantitative content analysis by Kim and Willis to analyze the American news media’s portrayal of individual and societal responsibility in obesity [ 49 ] and by Van den Bulck et al [ 50 ] to analyze the use of alcohol in the prime-time American youth TV series The OC .…”
Section: Introductionmentioning
confidence: 99%